The Effect of the 10-Valent Pneumococcal Nontypeable Haemophilus influenzae Protein D Conjugate Vaccine on H. influenzae in Healthy Carriers and Middle Ear Infections in Iceland - Sveinsdóttir, Hildigunnur (J Clin Microbiol, 2019)
Vaccinations with the 10-valent pneumococcal conjugated vaccine (PHiD-CV) started in Iceland in 2011. Protein D (PD) from H. influenzae, which is coded for by the hpd gene, is used as a conjugate in the vaccine and may provide protection against PD-positive H. influenzae. We aimed to evaluate the effect of PHiD-CV vaccination on H. influenzae in children, both in carriage and in acute otitis media (AOM). H. influenzae was isolated from nasopharyngeal swabs collected from healthy children attending 15 day care centers in 2009 and from 2012 to 2017 and from middle ear (ME) samples from children with AOM collected from 2012 to 2017. All isolates were identified using PCR for the hpd and fucK genes. Of the 3,600 samples collected from healthy children, 2,465 were culture positive for H. influenzae (68.5% carriage rate); of these, 151 (6.1%) contained hpd-negative isolates. Of the 2,847 ME samples collected, 889 (31.2%) were culture positive for H. influenzae; of these, 71 (8.0%) were hpd negative. Despite the same practice throughout the study, the annual number of ME samples reduced from 660 in 2012 to 330 in 2017. The proportions of hpd-negative isolates in unvaccinated versus vaccinated children were 5.6% and 7.0%, respectively, in healthy carriers, and 5.4% and 7.8%, respectively, in ME samples. The proportion of hpd-negative isolates increased with time in ME samples but not in healthy carriers. The number of ME samples from children with AOM decreased. The PHiD-CV had no effect on the proportion of the hpd gene in H. influenzae from carriage, but there was an increase in hpd-negative H. influenzae in otitis media. The proportions of hpd-negative isolates remained similar in vaccinated and unvaccinated children.